Aquatic Toxicology 1980
DOI: 10.1520/stp27410s
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Water Solubility, Soil Sorption, Octanol-Water Partitioning, and Concentration of Chemicals in Biota

Abstract: There is a need for a method of preliminary estimation of bioconcentration factors in fish and soil sorption coefficients for chemicals. A data base was assembled for 170 compounds having average values for these two parameters and also average values for water solubility and n-octanol-water partition coefficients. Binary regression equations between the logarithms of these values gave correlation coefficients that were all significant below the 1 percent level. Using these equations, measured average values f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(148 citation statements)
references
References 121 publications
4
143
0
1
Order By: Relevance
“…However, Koc is not available for all pesticides and can be computed using the relationship with water solubility (WS), proposed by Kenaga and Goring (1980), which is reliable for pesticides with solubility between 100 to 300 mg/L:…”
Section: Swat Algorithms For Pesticidesmentioning
confidence: 99%
“…However, Koc is not available for all pesticides and can be computed using the relationship with water solubility (WS), proposed by Kenaga and Goring (1980), which is reliable for pesticides with solubility between 100 to 300 mg/L:…”
Section: Swat Algorithms For Pesticidesmentioning
confidence: 99%
“…Most environmental research has explored the liquid-solid partitioning due to concerns regarding aquifer contamination and the assumption that soil particles are almost always coated with an aqueous film (Kenaga and Goring, 1980). However, with agricultural soil fumigation, researchers have found that volatilization of applied organic chemical pesticides is prevented by dry surface soils.…”
mentioning
confidence: 99%
“…The concentration of 238 U radionuclide depends on the quantity of the soil samples intake, volume of gastric fluid and intestinal fluid. The solubility of 238 U radionuclide also shows that the amount of 238 U radionuclide can be dissolved in gastrointestinal fluids and it shows the correlation between concentration and solubility [16]. According to US EPA [17], the average person ingests about 2 μg of uranium in food and water every day, but only a very small fraction of 1% or 2% is absorbed into the body.…”
Section: -4mentioning
confidence: 99%